Pengaruh Technology Acceptance Factor dan Website Service Quality terhadap Customer Loyalty dengan Customer Satisfaction sebagai Variabel Intervening : Studi Kasus Pada Ecommerce Traveloka di Yogyakarta - Sella Saputri; Henny Welsa; Nonik Kusuma Ningrum (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine how much influence Technology Acceptance Factor and Website Service Quality have on Customer Loyalty through Customer Satisfaction as Intervening Variables (Study on Traveloka E-commerce in Yogyakarta City). The population used in this study were consumers who had shopped at Traveloka. The sample in this study was 100 respondents using a quantitative approach, with purposive sampling technique. This data was taken using a questionnaire via the Google form, after the questionnaire results were collected, the data was tabulated using MS Excel and analyzed using multiple linear regression analysis using SPSS version 25. The results of this study indicate that Technology Acceptance Factor has a positive and significant effect on Customer Satisfaction. Website Service Quality has a positive and significant effect on Customer Satisfaction. Customer Satisfaction has no effect on Customer Loyalty. Technology Acceptance Factor has a positive and significant effect on Customer Loyalty. Website Service Quality has a positive and significant effect on Customer Loyalty. Effect of Technology Acceptance Factor on Customer Loyalty through Customer Satisfaction as an intervening variable is rejected. The effect of Website Service Quality on Customer Loyalty through Customer Satisfaction as an intervening variable is rejected. Keywords: Technology Acceptance Factor, Website Service Quality, Customer Loyalty, Customer Satisfaction.